2022
DOI: 10.3390/challe13020040
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Effects of Medicinal Plant (Azadirachta indica) Used as Forage and for Ethnoveterinary Practices: New Insights from Animal Models

Abstract: In some African and Asian countries, Azadirachta indica (AI) has been fed to livestock for decades and traditionally used to treat certain animal and human diseases. Recently, there are suspicions that the plant may possess anti-reproductive properties and concerns that the continued use of AI as forage or for folkloric medicine may detrimentally affect reproduction in the subjects. To address these challenges, this work determined the reproductive and fertility effects of a methanolic seed extract of AI (MSEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…The cell viability for AILE was found to be 66.214 µg/mL which exhibited no cytotoxic effect on the HCT116 cell line. This study agreed with Ngure et al (2009), Chaudhary et al (2017), andNjoga et al (2022) stated that AILE showed no observable signs of toxicity and proved to be safe for medical use.…”
Section: Discussionsupporting
confidence: 92%
“…The cell viability for AILE was found to be 66.214 µg/mL which exhibited no cytotoxic effect on the HCT116 cell line. This study agreed with Ngure et al (2009), Chaudhary et al (2017), andNjoga et al (2022) stated that AILE showed no observable signs of toxicity and proved to be safe for medical use.…”
Section: Discussionsupporting
confidence: 92%
“…Azadirachta indica methanolic seed extract inhibited reproduction in female albino rats. Its mechanism of action may be hormonal, specifically through the suppression of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) (Njoga et al 2022) [113] .…”
Section: Abortifacient Activity Of Medicinal Plantsmentioning
confidence: 99%
“…Azadirachta indica leaves are used to make an extract, a plant belonging to the Meliaceae family, was used in the current study will be used to create α-Fe2O3 NPs in a green manner. This Azadirachta indica plant has been used to treat numerous human disease problems since ancient times (Njoga et al 2022). The aqueous Azadirachta indica extract is used to make some NPs, including gold, zinc, cobalt, copper, silver, and other metal oxide (Patil et al 2022;Manjula et al 2022;.…”
Section: Introductionmentioning
confidence: 99%